Penanganan Tindak Pidana Viral: Reduksi Terhadap Asas Legalitas Ke Asas Viralitas - Muammar, Muammar (PATTIMURA Legal Journal, 2023)
Introduction: The handling of a number of criminal cases that have befallen victims and reported to the police, must first meet a number of dead ends. The justice that the victim expects from the case that happened to him must wait until the case goes viral and creates a reaction and public pressure. Purposes of the Research: This study aims to answer how to reduce and shift the principle of legality to the principle of "virality". This is because the handling of viral crimes first and then handled by the police has actually reduced and shifted the position of the principle of legality as the most fundamental principle in Indonesian criminal law. Methods of the Research: This study uses a normative research type. The approach used is a case approach, a statute approach and a conceptual approach. Results Originality of the Research: The results of the study show that the principle of legality as stipulated in Article 1 paragraph (1) of the Criminal Code which emphasizes that there is no act that can be punished without being regulated and stipulated in statutory regulations before the act is committed, has experienced reduction and shifted to nothing. an act that can be punished without going viral first. In other words, the principle of legality has been reduced from no criminal and criminal acts without prior law, to no criminal and criminal acts without going viral first.